Animal models of osteoarthritis: characterization of a model induced by Mono-Iodo-Acetate injected in rabbits. Issue 1 (1st January 2020) - Rebai, Mohamed Ali; Sahnoun, Nizar; Abdelhedi, Oussema; Keskes, Khaled; Charfi, Slim; Slimi, Fathia; Frikha, Rim; Keskes, Hassib
ABSTRACT: Knee Osteoarthritis is a considerable public health concern, both in terms of life quality and treatment financial impacts. To investigate this disease, animal models are deemed a promising alternative. In fact, although a perfect model is generally farfetched, the creation of models that simulate human disease as accurately as possible remains an important research stake. This study aims to highlight the usefulness of the model induced by injected Mono-Iodo-Acetate and to standardize it for the rabbit species. Osteoarthritis was induced by an infra-patellar injection of 0.2 ml of an MIA solution in the left knee of 24 female New Zealand rabbits. The right knee served as a control by receiving an injection of physiological serum. The rabbits were divided into 4 groups of 6 individuals each according to the dose of MIA received per knee. All rabbits were euthanized 30 days after the injection. After sacrifice, the knees were carefully dissected and macroscopic and microscopic scores of cartilage, meniscal and synovial lesions were attributed to each group. Our study followed the laboratory animal care and management guideline published in 2017 by the Canadian Council of Animal Care. The control knees of all rabbits showed no macroscopic or microscopic lesions. The macroscopic lesions: osteophytes, meniscal lesions, fibrillation and erosion of the cartilage and microscopic lesions: disorganization of the chondrocytes, decrease in proteoglycans and synovial inflammation clinically diagnosed in human pathology were all detected and were similarly reproducible among the knees of the same group. Through this work, we highlighted the merits of the arthritis model induced by MIA, namely its simulation of several aspects of human pathology. Further advantages are low cost, speed, reproducibility. This model notably avoids delicate and risky surgical operations.